Analysis of Junior High School Students' Multiple Mathematical Representation (MMR) Ability in Solving Fraction Problems - Luluk Faridah; Mustofa; Emmy Hamidah; Heny Ekawati Haryono (Riemann: Research of Mathematics and Mathematics Education, 2026)
This study aims to analyze the multiple representations of mathematics (MMR) of junior high school students with high, medium, and low abilities in solving fraction problems. This study uses a descriptive qualitative method. The subjects of this study were 6 students taken from 32 seventh-grade students of SMP Negeri 2 Sukodadi. The research instrument consisted of a problem-solving test and a semi-structured interview guide (task-based) that refers to the aspects of multiple representations, namely (1) symbolizing; (2) describing (visually, verbally, and symbolically); and (3) referring to the answer. Data were analyzed through data condensation, data presentation, and drawing conclusions, with time triangulation to ensure the validity of the findings. The results of the study show that, based on student scores and data obtained, students are in the high category; there are 11 students (34.375%), with an average score of 100. There are 10 students in the medium category (31.25%), with an average score of 62.5. And 11 students in the low category (34.375%), with an average score below 50. Based on the multiple representations used, 12.5% of students in the high category meet all indicators of multiple representations. 12.5% of students in the medium category meet 3 indicators, with 2 representations. 75% of students in the low category only meet 1 indicator (describing visually/verbally). These findings indicate the need for us to achieve success in solving mathematical problems.